Korean survey data reveals an association of chronic laryngitis with tinnitus in men. - Myung Jin Ban; Won Shik Kim; Ki Nam Park; Jae Wook Kim; Seung Won Lee; Kyungdo Han; Jae Won Chang; Hyung Kwon Byeon; Yoon Woo Koh; Jae Hong Park (PLoS ONE, 2018)
The association between chronic laryngitis and tinnitus is not a well-studied topic, unlike the association of these two conditions with many other disorders. Cross-sectional data of 11,347 adults (males: 4,934; females: 6,413), who completed the Korea National Health and Nutrition Examination Survey (KNHANES) from 2010 to 2012 were used to investigate this association. Lifestyle patterns, including smoking and alcohol habits, regular exercise, physical and mental health status, socioeconomic status, nutritional status, and other chronic diseases, were analyzed. Chronic laryngitis and tinnitus were diagnosed by field survey teams, which included otolaryngologists, who conducted chronic disease surveillance using a health status interview, a nutritional status questionnaire, and a physical examination. Chronic laryngitis was significantly associated with age, education beyond high school, depressed mood, voice change, metabolic syndrome, and tinnitus in men. In women, chronic laryngitis was associated with body mass index and diabetes mellitus. Chronic laryngitis in men was significantly associated with tinnitus (odds ratio 1.671, [95% confidence interval: 1.167-2.393]) after adjusting for age, body mass index, smoking status, alcohol intake, regular exercise, metabolic syndrome, education beyond high school, and depressed mood. Additionally, the prevalence of chronic laryngitis increased with increasing severity of tinnitus in men alone (P = 0.002). The study revealed a significant association between chronic laryngitis and tinnitus.